Implementation of the Merdeka Curriculum and Readiness of Educational Infrastructure in Elementary Schools - Syafruddin, Syafruddin; Suastra, I Wayan; Lasmawan, I Wayan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Education is a cornerstone in shaping competent and adaptable generations. Merdeka Curriculum was introduced as an educational reform effort in Indonesia to grant students the freedom to develop their potentials according to their interests and talents. However, the implementation of Merdeka Curriculum faces challenges, particularly in educational infrastructure readiness, especially at the primary school level. Adequate educational infrastructure, including physical facilities, access to information and communication technology (ICT), and availability of competent human resources, is crucial for the successful execution of this curriculum. This research aims to analyze the readiness level of educational infrastructure in primary schools to support the implementation of Merdeka Curriculum, identify challenges, evaluate the influence of infrastructure readiness on curriculum effectiveness, formulate strategic steps to address infrastructure constraints, and explore the roles of the government and relevant stakeholders in enhancing educational infrastructure readiness. The research methodology employed includes qualitative and quantitative descriptive methods, involving data analysis from questionnaires, interviews, and observations. Findings indicate that the majority of primary schools still face infrastructure challenges, with only a small portion possessing adequate facilities. Schools with better infrastructure tend to implement Merdeka Curriculum more effectively, evidenced by improved student participation and higher academic outcomes. Recommended strategic steps include increasing budget allocations, providing sufficient ICT devices, and conducting intensive teacher training. The government plays a crucial role in supporting educational infrastructure development through supportive policies and adequate budget allocations. Collaborative efforts among the government, private sector, and local communities are expected to expedite improvements in educational infrastructure readiness, thereby enabling all schools to effectively support Merdeka Curriculum.